An estimate of the stochastic gravitational wave background from the MassiveBlackII simulation. Issue 4 (14th February 2022) - Sykes, Bailey; Middleton, Hannah; Melatos, Andrew; Di Matteo, Tiziana; DeGraf, Colin; Bhowmick, Aklant
ABSTRACT: A population of supermassive black hole (SMBH) binaries is expected to generate a stochastic gravitational wave background (SGWB) in the pulsar timing array (PTA) frequency range of 10 −9 to 10^-7 Hz . Detection of this signal is a current observational goal and so predictions of its characteristics are of significant interest. In this work, we use SMBH binary mergers from the MassiveBlackII simulation to estimate the characteristic strain of the stochastic background. We examine both a gravitational wave (GW) driven model of binary evolution and a model which also includes the effects of stellar scattering and a circumbinary gas disc. Results are consistent with PTA upper limits and similar to estimates in the literature. The characteristic strain at a reference frequency of 1 yr^-1 is found to be A_yr^-1= 6.9 × 10^-16 and A_yr^-1= 6.4 × 10^-16 in the GW-driven and stellar scattering/gas disc cases, respectively. Using the latter approach, our models show that the SGWB is mildly suppressed compared to the purely GW-driven model as frequency decreases inside the PTA frequency band.